Childhood renal cell carcinoma - Nouval Shahab; Arry Rodjani; Rainy Umbas (Indonesian Pediatric Society, 2006)
Renal cell carcinoma (RCC) in children isseldom found. The incidence of thistumor in childhood is estimated to be 0.1-0.3% out of all neoplasms and 2-7% out ofall malignant renal tumors. The Third NationalCancer Survey reported an incidence of only four casesof RCC per year compared to 117 per year of Wilms’tumor.The incidence of RCC has not been reported inIndonesia. This is the first case of childhood RCCfound in our institution. To the best of our knowl-edge, this is the first report of childhood RCC in In-donesia.